2018
DOI: 10.1177/2045894018769305
|View full text |Cite
|
Sign up to set email alerts
|

Riociguat treatment for portopulmonary hypertension: a subgroup analysis from the PATENT‐1/‐2 studies

Abstract: In patients with portopulmonary hypertension (n = 13) included in the 12-week randomized placebo-controlled PATENT-1 trial, riociguat was well tolerated and improved 6-min walking distance (6MWD), World Health Organization functional class (WHO FC), and other efficacy parameters; 6MWD and WHO FC improvements were sustained over two years in the open-label extension, PATENT-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
2
18
0
4
Order By: Relevance
“…In addition, one patient died of sepsis related to bronchopneumonia, an event not ascribed to the study drug. (40)…”
Section: Soluble Guanylate Cyclase Stimulatormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one patient died of sepsis related to bronchopneumonia, an event not ascribed to the study drug. (40)…”
Section: Soluble Guanylate Cyclase Stimulatormentioning
confidence: 99%
“…Riociguat appeared to improve functional and hemodynamic determinations in patients with PoPH; however, some patients experienced side effects (headaches (n=3) and peripheral edema (n=3)). In addition, one patient died of sepsis related to bronchopneumonia, an event not ascribed to the study drug (40).…”
Section: Introductionmentioning
confidence: 99%
“…PATENT-2 showed sustained improvements in functional class and 6MWD (71). A recently published subgroup analysis of the 13 patients with PoPH who were enrolled in PATENT-1 and 2 showed similar improvements in WHO functional class, 6MWD and PVR (72). Importantly, riociguat was well-tolerated by the PoPH patients.…”
Section: Treatment Of Pophmentioning
confidence: 76%
“…For the first time, 13 patients with PoPH were included in the PATENT-1 trial with riociguat, a soluble guanylate-cyclase stimulator. Subgroup analysis was performed for patients with PοPH and showed that riociguat was well-tolerated and significantly improved World Health Organization functional class and the 6-min walking test after 12 weeks of treatment, while functional improvement was sustained for 2 years [103].…”
Section: Treatment and Prognosismentioning
confidence: 99%